Tinjauan Kriminologis Terhadap Tindak Pidana Penganiayaan Yang Dilakukan Narapidana Didalam Rumah Tahanan - M.Fatih Adityawarman; Sufirman Rahman; Nasrullah Arsyad (Qawanin Jurnal Ilmu Hukum, 2020)
This Research is aimed at students, especially law faculty students who want to carry out research related to criminal acts of torture committed by prisoners in the class I A detention center in Makassar City. Mistreatment of fellow prisonersnin the detention center, Researchers continue to try uncover what is the cause of the criminal act of persecution that occurs in the detention center and what efforts can be made by the Makassar City Detention Center Official. From the results of research that has been conducted by researchers, the researchers found what factors cause the crime of mistreatment that occurs in the detention center, namely inadequate room capacity, secondly, individual problems such as stealing clothes from fellow prisoners and love problems experienced by prisoners. Then as for the efforts that can be made by the remand center, namely providing legal counseling to the detainees, secondly giving spiritual cleansing to the detainees, thirdly not giving remissions to prisoners who committed a criminal act of torture, the fourth was put in solitary confinement. Abstrak Penelitian ini bertujuan untuk mengetahui tindak pidana penganiayaan yang dilakukan narapidana didalam rumah tahanan kelas I A Kota Makassar,penganiayaan sesama narapidana di rutan. Peneliti berusaha mengungkap apa penyebab terjadinya tindak pidana penganiayaan yang terjadi di rutan dan upaya apa saja yang bisa dilakukan petugas rutan dalam mengurangi tindak pidana penganiayaan. dari hasil penelitian yang telah dilakukan oleh peneliti, peneliti menemukan faktor faktor apa saja yang menyebabkan terjadinya tindak pidana penganiayaan yang terjadi didalam rutan yaitu seperti kapasitas kamar yang tidak memadai kedua yaitu masalah individu seperti saling mencuri pakaian sesama tahanan danmasalah percintaan yang dialami para tahanan, lalu adapun upaya yang dapat dilakukan pihak rutan yaitu melakukan penyuluhan hukum kepadapara tahanan yang kedua memberikan siraman rohani kepada para tahanan, ketiga tidak memberikan remisi kepada para tahanan yang melakukan tindak pidana penganiayaan,yang ke empat dimasukkan kedalam sel pengasingan.